How Long Can We Build It? Ensuring Usability of a Scientific Code Base - Klaus Rechert; Jurek Oberhauser; Rafael Gieschke (International Journal of Digital Curation, 2021)
Software and in particular source code became an important component of scientific publications and henceforth is now subject of research data management.  Maintaining source code such that it remains a usable and a valuable scientific contribution is and remains a huge task. Not all code contributions can be actively maintained forever. Eventually, there will be a significant backlog of legacy source-code. In this article we analyse the requirements for applying the concept of long-term reusability to source code. We use simple case study to identify gaps and provide a technical infrastructure based on emulator to support automated builds of historic software in form of source code.